Zero Action on Perfect Crystals for U_q(G_2^{(1)}) - Kailash C. Misra; Mahathir Mohamad; Masato Okado (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
The actions of 0-Kashiwara operators on the U_q(G_2^{(1)})-crystal B_l in [Yamane S., J. Algebra 210 (1998), 440-486] are made explicit by using a similarity technique from that of a U_q'(D_4^{(3)})-crystal. It is shown that {B_l}_{l ≥ 1} forms a coherent family of perfect crystals.